Evolution and Christian thought today - Mixter, Russell L.; American Scientific Affiliation (London, UK Paternoster, 1961)
Includes bibliographical references, index, charts and plates.
Paper from a symposium by members of the American Scientific Affiliation
Keywords: Christianity and evolution